Dental caries prevalence among inter-mediate and secondary school students in Thamar-Yemen - Faraed D Salman (University of Mosul, College of Dentistry, 2008)
Aims: To determine the prevalence of dental caries among intermediate and secondary school students 13-16 years old to determine the age and sex difference and to obtain data that can help in planning preventive dental health programs for school students in Yemen. Materials and Methods: A random sample of 512 intermediate school students,449 secondary school students were examined. Interme-diate school student sample was divided into 3 age groups namely 13,14,15 and secondary school stu-dent sample was divided into 3 age groups namely 16,17,18 years old. The WHO methodology (1997) was used to assess the individual tooth status. Results: The mean DMFT for the total sample was 5.2±0.13; which increased with the increasing of age from 4.54 to 4.84 to 6.47 for the age groups 13,14,15 years old respectively; without significant sex difference as total 5.44 for males and 5.14 for total females. Results of dental caries for the secondary school students showed that the mean DMFT for the total sample was 5.98± 0.14, which decreased with the increasing of age from 5.60 to 6.49 to 5.85 for the age groups 16,17,18 years old respectively, with peak value at 17 years old without signifi-cant sex difference, 5.74 for total males, 6.21 for total females. Conclusion: The mean DMFT for both intermediate, secondary schools increased with increasing age with statistical significant difference with no sex differences.